Efficacy of copper citrate in grapevine disease control - Aleksić, Goran A; Milićević, Zoran D; Kuzmanović, Slobodan; Starović, Mira; Stevanović, Miloš; Delibašić, Goran; Živković, Svetlana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2019)
The control of Plasmopara viticola and Botrytis cinerea, two of the most dangerous pathogens on grapevine, requires frequent treatments with chemicals based on weather conditions. Numerous applications of fungicides have resulted in developing fungicide resistance. Active ingredients based on copper have been used very successfully for a long time to protect grapevines against these pathogens. Application of a copper citrate formulation with high degree dissociation at a very low concentration (1%) was evaluated in field trials. The efficacy of two concentrations of copper citrate, 0.5 and 1.0%, were tested against P. viticola on grapevine in three locations, and against B. cinerea in two locations during 2018. Our results demonstrated that the concentration of 1.0% copper citrate was highly effective against P. viticola (87.4%) and B. cinerea (63.7%), compared to standard treatment (90.6 and 53.1%), under a high level of infection.
Keywords: grapevine; downy mildew; grey mould; fungicides; copper citrate